Biventricular Pacing in Congestive Heart Failure: Follow-up Data - Naik, N; Yadav, R; Juneja, R; Roy, A; Anandraja, S (Nepalese Heart Journal, 2004)
Biventricular (BV) pacing is a promising option for patients with advanced heart failure and electromechanical conduction delay. We present our experience in 17 patients. 19 patients underwent the implant procedure at our institute: 3 others had their implant elsewhere and were on our follow-up. The mean age was 46.6+10.7 years and 14 were males. A conventional indication for pacing was present in 8; 4 of them had previously received a pacemaker. All had severe LV dysfunction. The implant procedure was successful in 12/14- in one the CS lead could not be anchored satisfactorily and a dual chamber device was inserted.